Mekanisme Fisiologi Toleransi Cekaman Aluminium Spesies Legum Penutup Tanah terhadap Metabolisme Nitrat (NO3 - ), Amonium (NH4 + ), dan Nitrit (N02 - ) - M. Zulman Harja Utama (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The experiment was aimed to investigate the Al-tolerant mechanisms physiology of legume cover crops species related to metabolism NO3 - , NH4 + , and N02 - . The results revealed that an addition of Al had less effect on Al-tolerant species compared to Al-sensitive in term of reduction in NO3 - , NH4 + and N02 - uptake. The reduction in Nitrit of the Al-tolerant species under Al treatment was less than in Al-sensitive species. The results suggested that in tolerant legume cover crops species, the higher level of Al tolerance seems to have emanated from efficient NO3 - metabolism and the higher N02 - to NH4 + .